THE EFFECT OF ALTRUISM BEHAVIOR ON SOCIAL LOAFING IN PSYCHOLOGY STUDENTS OF 17 AUGUST 1945 UNIVERSITY SAMARINDA - Putri, Audi Nadia; Umaroh, Siti Khumaidatul; Imawati, Diana (LPPM Universitas 17 Agustus 1945 Samarinda, 2024)
Abstract: Under certain conditions, quite a lot of students are less involved in group activities, especially those related to academic assignments which are a shared responsibility. This often happens because there is a belief that the task will be completed by other group members. This research was conducted with the aim to find out the effect of altruistic behavior on social loafing in students at the Faculty of Psychology, University of 17 August 1945 Samarinda. About 111 active students in even semester were involved in this research. Research data were obtained using two types of scales, The Altruism Behavior Scale and The Social Loafing Scale. Simple regression analysis was used using SPSS 20 for Windows. Based on the results from analysis shown that there is about 33% effect of altruistic behavior on social loafing on Psychology students from the 17 August 1945 University Samarinda. Keywords: Altruism Behavior, Social Loafing, Psychology Faculty Students